2004
DOI: 10.3141/1899-14
|View full text |Cite
|
Sign up to set email alerts
|

Visual Information for Car Following by Drivers: Role of Scene Information

Abstract: An important task during driving is the maintenance of headway during car following. The visual information available to a driver for successful car following was examined. A model of car following that used the visual angle and change in visual angle of a lead vehicle was developed. The study examined whether information from the surrounding scene (e.g., the roadway and buildings) influenced car-following performance. Licensed drivers were presented with a car-following task in a driving simulator. The simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…It is unclear whether the DVA model would avoid a crash under these deceleration conditions. Third, we have found (Andersen, Sauer, & Saidpour, 2004) that drivers use surrounding scene information (presumably information regarding texture and edge rate to determine vehicle speed) in car following. An important issue for future research is to examine the utility of this information in detail and to incorporate such information in the DVA model.…”
Section: Discussionmentioning
confidence: 88%
“…It is unclear whether the DVA model would avoid a crash under these deceleration conditions. Third, we have found (Andersen, Sauer, & Saidpour, 2004) that drivers use surrounding scene information (presumably information regarding texture and edge rate to determine vehicle speed) in car following. An important issue for future research is to examine the utility of this information in detail and to incorporate such information in the DVA model.…”
Section: Discussionmentioning
confidence: 88%
“…Instead, distance and speed information is based on the driver's perception of distance and speed and thus dependent on visual information for distance and speed. Recently, Andersen and Sauer have proposed and tested a model [driving by visual angle (DVA) model] for car following based on visual information for distance and speed (3,4). Specifically, their model uses visual angle and change in visual angle as the primary source of information for maintaining distance and for detecting distance that was well within the range of visibility.…”
Section: Driving By Visual Anglementioning
confidence: 99%
“…The results of their study indicate that the DVA model, as compared to other car following models based on precise headway distance and LV speed, could better predict driver performance in both simulator and real world driving conditions. In a related study Andersen and Sauer (2005) showed that information of the driving scene was also used in car following. They presented drivers with an active car following task in which LV speed varied according to a complex waveform.…”
mentioning
confidence: 99%